A Novel, Single Algorithm Approach to Predict Acenocoumarol Dose Based on CYP2C9 and VKORC1 Allele Variants - Verde, Zoraida (Public Library of Science, 2010)
The identification of CYP2C9 and VKORC1 genes has strongly stimulated the research on pharmacogenetics of coumarins in the last decade. We assessed the combined influence of CYP2C9 *2 and *3, and VKORC1 c.-1639G>A, 497C>G, and 1173C>T variants, on acenocoumarol dosage using a novel algorithm approach, in 193 outpatients who had achieved stable anticoagulation. We constructed an “acenocoumarol-dose genotype score” (AGS, maximum score = 100) based on the number of alleles associated with higher acenocoumarol dosage carried by each subject for each polymorphism. The mean AGS was higher in the high-dose (>28mg/week) compared with the low-dose (<7mg/week) group (mean(SEM) of 84.1±3.4 vs. 62.2±4.8, P = 0.008). An AGS>70 was associated with an increased odds ratio (OR) of requiring high acenocoumarol dosage (OR: 3.347; 95%CI: 1.112–10.075; P = 0.032). In summary, although more research is necessary in other patient cohorts, and this algorithm should be replicated in an independent sample, our data suggest that the AGS algorithm could be used to help discriminating patients requiring high acenocoumarol doses to achieve stable anti-coagulation.